The effects of climate change on women in Guruve district - Mudzimurega, Melody V. (Midlands State University, 2017)
The thrust of this study was to examine the effects of climate change on women in Guruve district ward 20. Purposive sampling under qualitative research was used to collect data from the targeted population which was women, Agricultural extension officers, the village head and the general populace. Interviews, focused group discussions and observations were the instruments used to collect the data. The researcher found out that climate change has disproportionately affected people in the community with women being mostly affected. This was due to their dependency on natural local resources, limited access to land, lack of information on climate change, reproductive role burden and lack of collateral to secure loans. The research also reveals that climate change affects the attainment of Sustainable Development Goals (SDGs) as it affects food security. Climate change has also exacerbated the gender disparities. Therefore there is need for economic empowerment of women because they are the most affected and there is need for gender analyses in all climate change policies, programs, projects and budgets. This helps in creating gender sensitive policies. NGOs should complement the government in empowering women in climate change coping and adaptation strategies. Recommendations to address the effects of climate change in ward 20 includes growing of drought resistant crops, land ownership by women, involvement in decision making and practicing of off-farm activities so as to generate income rather than relying on agriculture alone.